A movement without marches African American women and the politics of poverty in postwar Philadelphia - Levenstein, Lisa (John Hope Franklin series in African American history and culture, 2009)
Lisa Levenstein reframes highly charged debates over the origins of chronic African American poverty and the social policies and political struggles that led to the postwar urban crisis. A Movement Without Marches follows poor black women as they traveled from some of Philadelphia's most impoverished neighborhoods into its welfare offices, courtrooms, public housing, schools, and hospitals, laying claim to an unprecedented array of government benefits and services. With these resources came new constraints, as public officials frequently responded to women's efforts by limiting benefit
Keywords: African American women : Pennsylvania : Philadelphia : History : 20th century; Poor women : Pennsylvania : Philadelphia : History : 20th century; African American women : Pennsylvania : Philadelphia : Social conditions : 20th century; African American women : Pennsylvania : Philadelphia : Biography; African Americans : Pennsylvania : Philadelphia : Economic conditions : 20th century; Poverty : Political aspects : Pennsylvania : Philadelphia : History : 20th century; Urban policy : Pennsylvania : Philadelphia : History : 20th century; Philadelphia (Pa.) : Race relations : History : 20th century; Philadelphia (Pa.) : Politics and government : 20th century; Philadelphia (Pa.) : Social conditions : 20th century